Active Vibration Control To Attenuate Hand-Arm Vibration For Orbital Sander - Ahmad Mazlan, Ahmad Zhafran (2012)
Dynamic analysis of the orbital sander is carried out using coupled orbital sander-hand-arm model subjected to the active vibration control (AVC) pad. Analisis dinamik bagi mesin penggilap orbit telah dilakukan dengan menggunakan model pasangan mesin penggilap orbit dan tangan tertakluk kepada pad kawalan getaran aktif